Adsorption capacity of agroindustrial waste to remove contaminants from wastewater - Paccha Rufasto, Cesar Augusto (2023)
Agroindustrial residues are among the lowest cost biomass inputs, these are currently the most applied for the elimination of pollutants in wastewater. This article makes a compilation of the latest experimental findings presented with different organic materials. In this study, the adsorbents were classified based on their preparation technique as: unmodified biosorbent, premodified biosorbent, chemically modified biosorbent, and physically modified biosorbent. It was observed that orange peel, coconut, rice and chestnut are the species with the best results in the adsorption studies. The contaminants adsorbed by these carbons have been more on metals and dyes. Said review showed the good adsorption capacities of the carbons obtained through agro-industrial residues for the adsorption of heavy metals, dyes, pesticides and other contaminants. It was also observed that agro-industrial residues have a high potential for reuse, which underlines their usefulness for industrial application.